High‐Contrast Optical Modulation from Strain‐Induced Nanogaps at 3D Heterogeneous Interfaces. Issue 11 (26th April 2020) - Cho, Donghwi; Shim, Young‐Seok; Jung, Jae‐Wook; Nam, Sang‐Hyeon; Min, Seokhwan; Lee, Sang‐Eon; Ham, Youngjin; Lee, Kwangjae; Park, Junyong; Shin, Jonghwa; Hong, Jung‐Wuk; Jeon, Seokwoo
Abstract: The realization of high‐contrast modulation in optically transparent media is of great significance for emerging mechano‐responsive smart windows. However, no study has provided fundamental strategies for maximizing light scattering during mechanical deformations. Here, a new type of 3D nanocomposite film consisting of an ultrathin (≈60 nm) Al2 O3 nanoshell inserted between the elastomers in a periodic 3D nanonetwork is proposed. Regardless of the stretching direction, numerous light‐scattering nanogaps (corresponding to the porosity of up to ≈37.4 vol%) form at the interfaces of Al2 O3 and the elastomers under stretching. This results in the gradual modulation of transmission from ≈90% to 16% at visible wavelengths and does not degrade with repeated stretching/releasing over more than 10 000 cycles. The underlying physics is precisely predicted by finite element analysis of the unit cells. As a proof of concept, a mobile‐app‐enabled smart window device for Internet of Things applications is realized using the proposed 3D nanocomposite with successful expansion to the 3 × 3 in. scale. Abstract : Mechano‐responsive smart windows are developed using stretchable 3D hybrid nanocomposites. The inserted periodic oxide nanoshell in the elastomer offers formation of light scattering air gaps upon stretching, and this provides high‐contrast optical modulation. It is demonstrated that smart window devices can be prepared for self‐responding to the surrounding environments and temporary projection screens by integrating with Internet of Things technology.